Pedagogy of Action in Practice - Šernas, Vytautas (Acta Paedagogica Vilnensia, 1996)
The aim of education is not only to provide knowledge, but also to provide necessary skills, to teach pupils how to apply the acquired knowledge in practice. The article discusses the structure of the process of action and historical development of this branch of pedagogy. The principles of learning by doing are also analysed. Forms and methods of activating pupils are presented. The article also speaks about possibilities of application of pedagogy of action in Lithuania. Pedagogical requirements for learning by action are presented in the final chapter of the article.
Keywords: History of education; pedagogy of action; methods of teaching; a student activity; learning by doing.